Antimicrobial and insect antifeedant activities of some Tröger’s bases - G. Thirunarayanan (Arabian Journal of Chemistry, 2017)
A series of substituted Tröger’s bases (2,8-dimethyl-6H, 12H- 5,11-methanodibenzo[b, f][1,5] diazocines) have been synthesized and resolved. These bases are characterized by their physical constants, micro analyses, IR, NMR and mass spectral data. The antimicrobial and insect antifeedant activities of these Tröger’s bases have been screened.